Ovid und die Musik - Albrecht, Michael von (Scripta classica Israelica, 1996)
Based on the Metamorphoses and the Art of Love, references to various genres of music and musical instruments are discussed. Further themes are the psychological, magic and pedagogical effects of music, its relevance to the domain of intellect (e.g. philosophy) and its relationship to poetry.
Elektronische Reproduktion der Druckausgabe
Gesehen am 10.10.2023